The Effect Of Customer-Product Compatibility On Intention To Purchase And Intention To Recommend Influencers With Attitude As An Intervening Variable: A Case Study On Uniqlo Instagram - Marsha Diva Saputri; Soepatini Soepatini (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research examines the influence of customer-product fit on purchase intention and intention to recommend influencers with attitude as an intervening variable. The aim of this research is to understand consumers' behavioral intentions when they find recommendations for Uniqlo fashion products from influencers on Instagram. With the phenomenon that we raise regarding the harmony between marketing that occurs with influencers which can influence the role of an influencer who uses social media to influence consumers (followers) and the Uniqlo brand. The method used in this research is a quantitative research method, and sample selection uses a purposive sampling approach. This research was conducted on the general public, especially Instagram social media users. This research used a sample of 161 respondents who met the testing requirements because they had passed the data checking stage. Where the data is measured numerically and uses Structural Equation Modeling with Partial Least Square. This program uses SmartPLS 3.2. The results of this research are that customer-product compatibility has a significant effect on influencers, customer-product compatibility has a significant effect on attitudes, customer-product compatibility has a significant effect on purchase intention and recommendation intention. The conclusion in this research is that all variables X have a significant influence on variable Y.